2011
DOI: 10.1161/strokeaha.110.605840
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Limb Preconditioning After Subarachnoid Hemorrhage

Abstract: Background and Purpose Making a limb transiently ischemic has been shown to induce ischemic tolerance in a distant organ. This phenomenon is known as remote ischemic limb preconditioning. We conducted a Phase IB study of remote ischemic limb preconditioning to determine the safety and feasibility of increasing durations of limb ischemia in patients with subarachnoid hemorrhage. Methods Patients with aneurysmal subarachnoid hemorrhage underwent limb preconditioning every 24 to 48 hours for 14 days. Limb preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 36 publications
4
110
0
1
Order By: Relevance
“…The results of our questionnaire analysis are consistent with other studies. 12,34,35 We could not detect any adverse effect on hematoma volume in patients presenting with PICH, and there were no excess mortality in the group treated with rPerC. Other studies have not reported on bleeding problems caused by or worsened by rPerC.…”
Section: Strokementioning
confidence: 64%
“…The results of our questionnaire analysis are consistent with other studies. 12,34,35 We could not detect any adverse effect on hematoma volume in patients presenting with PICH, and there were no excess mortality in the group treated with rPerC. Other studies have not reported on bleeding problems caused by or worsened by rPerC.…”
Section: Strokementioning
confidence: 64%
“…The BAIPC treatment consisted of 5 cycles of simultaneous bilateral upper arm ischemia for 5 min followed by reperfusion for another 5 min, performed twice daily for 180 consecutive days. The BAIPC procedure was performed using an electric autocontrol device with cuffs that inflated to a pressure of 200 mmHg during the ischemic period (patent number ZL200820123637.X, China) [18,26]. At the end of the BAIPC treatment, all devices were donated to the patients enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Control participants (n=28) underwent a sham BAIPC procedure during which bilateral upper arm cuffs were inflated to a pressure of 30 mmHg for 5 min, followed by 5 min of relaxation of the cuffs, for a total of 5 cycles twice daily for 180 consecutive days [18,26]. Aside from the preset cuff pressure during ischemia, the BAIPC and sham BAIPC devices were similar in both appearance and function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small clinical studies are ongoing to test the role of rIPC in protecting the brain against delayed ischemic injury after subarachnoid hemorrhage [4]. Recently, the value of rIPC as an adjunct therapy to thrombolysis in patients with ischemic stroke was investigated in an open-label, blinded-outcome, proof-of-concept study.…”
mentioning
confidence: 99%